2005
DOI: 10.1254/jphs.fp0040774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AF-DX116 and Other Muscarinic Receptor Antagonists on Orthostatic Hypotension in Autonomic Imbalanced (SART-Stressed) Rats

Abstract: Abstract. SART (specific alternation of rhythm in temperature)-stressed rats are an animal model of autonomic imbalance created by exposing animals to repeated cold stress. The SARTstressed rats have been shown to easily develop orthostatic hypotension (OH). In this study, effects of AF-DX116, a selective M 2 antagonist, and other muscarinic receptor antagonists on OH were investigated in SART-stressed and unstressed rats. Each anesthetized rat was canulated into the left common carotid artery, and blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…)-anesthetized rats were restrained on a board in a supine position according to our previous report. 2) In the paper, blood pressure, heart rate and tilting parameters obtained from carotid arteries were reported to be similar to those obtained from the femoral arteries, and difference of parameters between unstressed and SART-stressed rats was large and clear in the data from carotid arteries compared to those from femoral arteries. Then the carotid artery was used in this paper.…”
Section: Experimental Animalsmentioning
confidence: 73%
See 4 more Smart Citations
“…)-anesthetized rats were restrained on a board in a supine position according to our previous report. 2) In the paper, blood pressure, heart rate and tilting parameters obtained from carotid arteries were reported to be similar to those obtained from the femoral arteries, and difference of parameters between unstressed and SART-stressed rats was large and clear in the data from carotid arteries compared to those from femoral arteries. Then the carotid artery was used in this paper.…”
Section: Experimental Animalsmentioning
confidence: 73%
“…It has been reported that SART-stressed rats are in the state of continuous hypotension 1) and tachycardia, 15) and have greater drop in blood pressure at standing (MD), lower %re-flex and tend to have OH more easily. 2,19) The compensatory reflex mechanism, which should work against hypotension caused by tilting, is thought to be abnormal in the stressed rats. In the present study, the role played by the autonomic nervous system, particularly b-adrenoceptors, was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations